Application of TLC-based metabolomics to identify bioactive compounds possessing adenosine A1 receptor binding activity in Misai Kucing (Orthosphon stamineus) leaves - Khatib, Alfi; Yuliana, Nancy Dewi (2013)
A novel approach to identify compounds possessing adenosine A1 receptor binding activity in the leaves of Misai kucing (Orthisphon stamineus) was developed. In this study, adenosine A1 receptor binding, which is related to the diuretic action in the treatment of kidney stones was tested. A combination of thin layer chromatography of different extracts prepared by extraction with diverse solvents (n-hexane, chloroform, n-butanol and water), and multivariate data analysis based on orthogonal partial least squares proved to be a promising approach to determine these active compounds. Several methoxy flavonoids, fatty acids or terpenoids were estimated to be related o this activity. The results of this study support the traditional use of O. stamineus to treat kidney stone in Malaysia.